Analysis of The Relationship between Practices and Performance of Green Supply Chain Management in Indonesian Micro, Small, and Medium Enterprises (MSMEs) - Siregar, Dinda Halimah; Pinagara, Fajar Ayu (UI Scholars Hub, 2022)
Research Aims: This study discusses the practice of green supply chain management (GSCM) on environmental performance and operational costs in micro, small and medium enterprises (MSMEs) in Indonesia's food and beverage industry. Especially to examine the existence of ecocentricity and supply chain traceability that moderates GSCM practices with environmental performance and operational costs. Design/Methodology/Approach: The judgement sampling method was used in this study, and 85 respondents contributed. Research questionnaires were distributed online, and data were analysed using Partial Least Square-Structural Equation Modelling (PLS-SEM). Research Findings: The results of this study indicate that GSCM practices have a significant relationship to environmental performance and operational costs of MSMEs in the food and beverage industry in Indonesia. Supply chain ecocentricity moderates the relationship between GSCM practices, environmental performance, and operating costs. However, supply chain traceability does not moderate the relationship between GSCM practices, environmental performance, and operational costs. Theoretical Contribution/Originality: The concept and practice of GSCM is gaining popularity in developing countries, but is still limited to the scope of MSMEs. Thus, research on GSCM still has to be extended to MSMEs because most research is limited to large organisations. Managerial Implication in the South East Asian Context: This research covers the concept and practice of GSCM on MSMEs in Indonesia. For MSMEs in the food and beverage industry, this research is expected to be taken into consideration in implementing GSCM for supply chain ecocentricity to improve business performance. Research Limitation & Implications: Respondents are limited to the Java and Bali area and the food and/or beverage industry group.